Preparation and characterization of chitosan/zeolite composites for Reactive Orange 122 dye removal from aqueous media: isotherm and kinetic studies - Sanli, Gokmen T.; Demirhan, Elcin (SPRINGER HEIDELBERG, 2025)
The present study aimed to reduce environmental pollution by using a natural and cheap adsorbent for the removal of Reactive Orange 122, an anionic dye harmful to the environment, from wastewater in the textile industry. The zeolite mineral, abundant in Turkey, easily accessible, and cost-effective, was first utilized for this purpose. However, it was concluded that sufficient adsorption was not provided in the treatment of reactive dyes due to the structure of the natural zeolite mineral. Therefore, to increase the adsorption efficiency of zeolite minerals, published techniques were utilized to modify it with chitosan, and chitosan/zeolite composite was prepared. The adsorbents were characterized by using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and Brunauer-Emmett-Teller (BET) analysis. The study also examined the influence of various parameters including pH, contact time, and temperature on the adsorption of RO122 dye. Furthermore, the adsorption equilibrium was analyzed by evaluating kinetic and isotherm models. In comparison to the pseudo first-order model, the pseudo-second-order model was determined to be the best-fitting model with a coefficient of determination of 0.999. The study also examined two isotherm models, namely Langmuir and Freundlich, to adjust the equilibrium data to achieve optimal alignment. The Freundlich model demonstrated superior efficacy as an adsorption isotherm compared to the Langmuir isotherm model, as evidenced by a coefficient of determination (R2) of 0.9941.
Keywords: Reactive Orange 122; Chitosan; Zeolite; Adsorption; Kinetic; Isotherm; WASTE-WATER; ZEOLITES; FTIR; Energy & Fuels; Engineering